World Travelers: Parthenogenesis and Ecological Tolerance Enable Multiple Colonization Events by the Widespread Short-Tailed Whipscorpion, Stenochrus portoricensis (Schizomida: Hubbardiidae). Issue 1 (28th January 2022) - Monjaraz-Ruedas, Rodrigo; Francke, Oscar F; Prendini, Lorenzo
Abstract: Whereas morphology remains a powerful tool for the diagnosis and description of short-tailed whip scorpions, or schizomids (Order Schizomida Petrunkevitch, 1945), especially when adults of both sexes are available, the systematics of some schizomid taxa is difficult to resolve due to a lack of characters in these morphologically conserved arachnids. Stenochrus portoricensis Chamberlin, 1922, defined on a single character of the female spermathecae, is the most widespread schizomid in the New World. Numerous records in the Neotropics, from the southern United States to Brazil, throughout the Caribbean, and further afield, including the Galapagos Islands and Europe, raise the question as to whether S. portoricensis is indeed a single widespread species or a complex of multiple species with conserved morphology? The present study uses a multilocus dataset and the broadest geographical sample currently available to address the phylogeography of S. portoricensis with molecular divergence dating and ancestral area reconstruction of all currently known species of Stenochrus Chamberlin, 1922. Analyses recovered S. portoricensis as paraphyletic. Two species previously synonymized are revalidated and transferred to Stenochrus . Population structure analyses recovered the remaining samples of S. portoricensis as a single monophyletic species with low genetic divergence and comprising two subclades. Ancestral area reconstruction suggests a Mesoamerican origin for Stenochrus, which contains a widespread species, recently introduced to multiple localities. Introductions to Europe and the Caribbean occurred from a single clade in the Yucatán Peninsula, Mexico, within which genetic divergence is minimal, confirming the hypothesis of multiple independent introductions with successful colonization facilitated by parthenogenetic reproduction. Graphical Abstract: